Access to Preferential Loans for Poverty Reduction and Rural Development: Evidence from Vietnam. Issue 1 (2nd January 2018) - Nguyen, Lan Thanh; Hoai Nguyen, Anh Pham; van Passel, Steven; Azadi, Hossein; Lebailly, Philippe
Abstract: Preferential loans play an important role in the process of reducing poverty in developing countries. Considering the data set from the 2010 Vietnam Household Living Standards Survey, we aim to examine the influential factors in probability of households getting access to preferential loans. Additionally, we analyze the determinants of household income in association with the loans by applying a quantile regression model. Our results show that ethnicity-related factors have the largest marginal effect on the access to preferential loans. The results from the quantile regression model demonstrate that the debt factor has a deeper impact on the borrowing group at the lower quantiles of household income.